Private University Competitiveness Model Based on Resource Based View (Architecture Image Studies, 2026)
This study aims to analyze the competitiveness of Private Higher Education Institutions (PTS) in Kendari City through the Resource-Based View (RBV) perspective and an integrative theoretical framework that includes institutional theory, contingency theory, and Porter's theory. The study uses a qualitative descriptive approach with data collection through in-depth interviews, observations, and institutional document reviews. The results show that the competitive advantage of PTS in Kendari stems from a combination of valuable, rare, inimitable, and organized (VRIO) internal resources, such as lecturer quality, leadership, facilities, superior curriculum, and external partnership networks. However, limited funding, varying human resource quality, and public perception are major obstacles in creating sustainable excellence. The resulting integrative model shows that PTS competitiveness depends not only on internal resource management, but also on institutional legitimacy, adaptation to external dynamics, and cross-sector collaborative strategies. These findings provide theoretical contributions in extending the RBV to the dynamic and contextual context of higher education, as well as practical implications for strengthening PTS resource and collaboration strategies.